Շամախու գավառի գյուղերի պատմությունից - Ս. Գ. Կարապետյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Изучение сохранившихся историко-архитектурных памятников, летописных и архивных данных показывает, что гавар Шамахи (Ширван) вместе с окружающими гаварами уже в древние времена был заселен армянами. A study of preserved historical and architectural monuments, data of chronicles and archives shows that the district of Shamakhi and its surrounding regions were, already in ancient times, inhabited by Armenians.
Keywords: History; Auxiliary Sciences of History; Geography; Anthropology; Recreation; Demography; Population; Vital Events; Geography; Inscriptions; Epigraphy; D History; H Social Sciences; N Fine Arts; NA Architecture